Pergulatan Politik Identitas Partai-partai Politik Islam: Studi tentang PAN, PKB dan PKS - Yeby Ma’asan Mayrudin; M. Chairil Akbar (Universitas Islam Darul Ulum Lamongan, 2019)
This study seeks to conduct a critical analysis of the vision and practice of PoliticalIslam held by the leading Islamic parties in Indonesia, the National Mandate Party (PAN), theNational Awakening Party (PKB) and the Prosperous Justice Party (PKS). Strategy and themethods adopted by the three parties are not always based linearly with Islamic style. Theanalysis will be directed at explaining their adaptive actions and changes in response to theconcrete political realities and developments. Political Islam will be placed in the context notonly in terms of identity and ideological elements but also in its intersection with efforts toachieve the targets of political power and success in general elections both in a short-termand a long term. The authors believe that the theme of Political Islam is very interesting after observingthe phenomenon of national politics especially since 2017. Strengthened Islamic identitysentiment over the past two years through the National Movement of Guarding MUI Fatwa orGNPF-MUI has undeniably attracted more public attention. Political mobilization against thecase of blasphemy by the Governor of Jakarta at that time had opened crucial political spaces.Thus, the struggle for identity politics in Indonesia has become more dynamic and furtherstudy or research is highly needed. The development of the Islamic party in Indonesia to acertain degree shows the irony and paradox.